2011
DOI: 10.1371/journal.pone.0026963
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Coupling of Oxidative Phosphorylation In Vivo Precedes Electron Transport Chain Defects Due to Mild Oxidative Stress in Mice

Abstract: Oxidative stress and mitochondrial function are at the core of many degenerative conditions. However, the interaction between oxidative stress and in vivo mitochondrial function is unclear. We used both pharmacological (2 week paraquat (PQ) treatment of wild type mice) and transgenic (mice lacking Cu, Zn-superoxide dismutase (SOD1−/−)) models to test the effect of oxidative stress on in vivo mitochondrial function in skeletal muscle. Magnetic resonance and optical spectroscopy were used to measure mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 53 publications
6
47
0
Order By: Relevance
“…These have the potential to cause oxidative stress, which might mediate the trade-off between reproduction and lifespan (Dowling and Simmons, 2009;Monaghan et al, 2009). Although this is still a topic of great debate, several hypotheses have tried to link mitochondrial activity and ROS production (Brand, 2000;Balaban et al, 2005;Speakman, 2008;Neretti et al, 2009;Siegel et al, 2011). Two different hypotheses can be put forward to relate our results to ROS production.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These have the potential to cause oxidative stress, which might mediate the trade-off between reproduction and lifespan (Dowling and Simmons, 2009;Monaghan et al, 2009). Although this is still a topic of great debate, several hypotheses have tried to link mitochondrial activity and ROS production (Brand, 2000;Balaban et al, 2005;Speakman, 2008;Neretti et al, 2009;Siegel et al, 2011). Two different hypotheses can be put forward to relate our results to ROS production.…”
Section: Discussionmentioning
confidence: 97%
“…ROS have long been considered a by-product of mitochondrial respiration, which cause damage to macromolecules and cellular dysfunction. However, more recent studies have now demonstrated that ROS are potential regulators of a number of intracellular pathways (St-Pierre et al, 2006;Han et al, 2008;Rasbach and Schnellmann, 2007;Siegel et al, 2011;Finkel, 2012;Ray et al, 2012). Recently, using the same set of mice, we demonstrated that livers of reproductive females showed higher activity of superoxide dismutase (SOD) relative to non-reproductive females, as well as decreased protein oxidation (Garratt et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EDL and SOL muscles were dissected, and either flash‐frozen in liquid nitrogen or a mitochondrial extract derived from equivalent muscle weight/buffer volume was prepared as previously described (Siegel et al ., 2011). Briefly, muscle tissue was mechanically disrupted in phosphate buffer, and mitochondria were enriched by dual‐step differential centrifugation and resuspended in appropriate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the process Novel Prospects in Oxidative and Nitrosative Stressof peroxidation can inhibit the activity of protein transporters and ion channels [89,91]. The increase of the permeability also seems to occur in internal mitochondrial membrane, uncoupling respiratory-chain phosphorylation [93]. Finally, the lipid peroxidation leads the severe damages: modification of membrane permeability, enzymatic inhibitions, inactivation of transporters [37,92].…”
Section: Effects On Biological Membranesmentioning
confidence: 99%